Determinación de metabolitos secundarios de Solanum sessiliflorum, Capsicum annuum y Mansoa alliacea por métodos espectrofotométricos - Villasis Ipanama, Linda Isabel (2022)
The peruvian Amazon continues to generate a great contribution of plant species with ethnomedicinal benefits; It is for this reason that the objective of this study was to determine total polyphenols, saponins and alkaloids from the peel of Solanum sessiliflorum fruit, Capsicum annuum fruit and Mansoa alliacea leaves, by applying spectrophotometric methods. The values obtained for phenolic compounds are more representative in fruits of S. sessiliflorum (peel) that obtained higher results 24916.833 mg/100g for total phenols, flavonoids 45.738 mg/100g, anthocyanins 15.017 mg/100g and catechins a value of 0.004 mg /100g. In alkaloids, S. sessiliflorum presented 33.90 mg/100g, the fruit of C. annuum 20.32 mg/100g and the leaves of M. alliacea 17.34 mg/100g. For saponins, S. sessiliflorum obtained 161.40 mg/100g, C. annuum 51.75 mg/100g and M. alliacea 116.12 mg/100g; thus concluding that S. sessiliflorum is the most representative plant species in quantification of secondary metabolites.